Facies heterogeneity and source potential of carbonate-mudstone-dominated distal ramp deposits, Agrio Formation, Neuquén Basin, Argentina - Moore, Shawn (2020)
Fil: Moore, Shawn. Department of Geology and Geophysics, University of Utah. Estados Unidos.